An experimental verification of numerical model on superheated steam drying of Belchatow lignite. Issue 3 (September 2016) - Zakrzewski, M; Sciazko, A; Komatsu, Y; Akiyama, T; Hashimoto, A; Kaneko, S; Kimijima, S; Szmyd, J S; Kobayashi, Y
Abstract: Due to low production costs, lignite is an important component of energy mixes of countries in its possession. However, high moisture content undermines its applicability as fuel for power generation. Drying in superheated steam is a prospective method of upgrading quality of lignite. The study aimed to validate the drying model of lignite from Belchatow mine in Poland. The experimental investigation on superheated steam drying of lignite was previously conducted. Spheres of 10 mm in diameter were exposed to the drying medium at the temperature range of 110-170 o C. The drying behaviour was described in the form of moisture content, drying rate and temperature profile curves against time. With the application of basic coal properties (e.g. density, water percentage, specific heat) as well as the mechanisms of heat and mass transfer in subsequent stages of the process, the numerical model of drying was constructed. It was tentatively verified with reference to experimental results both in terms of drying parameters and temperature. The model illustrated drying behaviour in the entire range of conditions. Nevertheless, further development of numerical model is desirable regarding accuracy of the process parameters.